Enhancing drought resilience with conjunctive use and managed aquifer recharge in California and Arizona. (8th March 2016) - Scanlon, Bridget R; Reedy, Robert C; Faunt, Claudia C; Pool, Donald; Uhlman, Kristine
Abstract: Projected longer-term droughts and intense floods underscore the need to store more water to manage climate extremes. Here we show how depleted aquifers have been used to store water by substituting surface water use for groundwater pumpage (conjunctive use, CU) or recharging groundwater with surface water (managed aquifer recharge, MAR). Unique multi-decadal monitoring from thousands of wells and regional modeling datasets for the California Central Valley and central Arizona were used to assess CU and MAR. In addition to natural reservoir capacity related to deep water tables, historical groundwater depletion further expanded aquifer storage by ∼44 km 3 in the Central Valley and by ∼100 km 3 in Arizona, similar to or exceeding current surface reservoir capacity by up to three times. Local river water and imported surface water, transported through 100s of km of canals, is substituted for groundwater (≤15 km 3 yr −1, CU) or is used to recharge groundwater (MAR, ≤1.5 km 3 yr −1 ) during wet years shifting to mostly groundwater pumpage during droughts. In the Central Valley, CU and MAR locally reversed historically declining water-level trends, which contrasts with simulated net regional groundwater depletion. In Arizona, CU and MAR also reversed historically declining groundwater level trends in active management areas. These rising trends contrast with current declining trends in irrigated areas that lack access to surface water to support CU or MAR. Use of depleted aquifers as reservoirs could expand with winter flood irrigation or capturing flood discharges to the Pacific (0–1.6 km 3 yr −1, 2000–2014) with additional infrastructure in California. Because flexibility and expanded portfolio options translate to resilience, CU and MAR enhance drought resilience through multi-year storage, complementing shorter term surface reservoir storage, and facilitating water markets.